Copyright Act License for Commercial Broadcasting of 2014 World Cup Matches - Zidan, Abdul Hakim; Hidayatulloh, Hidayatulloh (Jurnal Kepastian Hukum dan Keadilan, 2022)
This study intends to determine the legal protection of copyright as licenses for broadcast copyrighted world cup works. Specifically, this study investigates the legal protection criteria for licenses registered with the Directorate General for Intellectual Property Rights. In addition, it attempts to examine instances of court decisions relating to copyright licensing issues. This study employs normative research and literature in accordance with a statutory methodology. As described in Article 83, paragraph 1, of the Copyright Law No. 28 of 2014, copyright certainty is established if the copyright has been registered with the Directorate General for Intellectual Property Rights. In order for the license agreement to have legal repercussions for third parties, it must be registered, but in practice it cannot be executed because there are no penalties for third parties that break the license. Similarly, in the instance of copyright infringement, the Judicial Review decision No. 43 PK/Pdt.Sus-HKI/2017 is one of them. FIFA recognized PT Inter Sports Marketing as the exclusive licensee for the 2014 World Cup in Brazil, as the company had registered. Due to violations by a Semarang hotel, the verdict did not reflect the losses sustained. It seemed as though the registration had been in vain since it lacked sufficient legal clarity.